Fashion theory : a reader - Barnard, Malcolm, 1958- (London ; New York : Routledge, 2007)
This collection of essays surveys and contextualises the ways in which a wide range of disciplines have used different theoretical approaches to explain, and sometimes to explain away, the variety, complexity and beauty of fashion.
Fashion and fashion theories -- Fashion and history/fashion in history -- What fashion is and is not -- What fashion and clothing do -- Fashion as communication -- Fashion: identity and difference -- Fashion clothes and the body -- Production and consumption -- Modern fashion -- Post-modern fashion -- Fashion and (the) image -- Fashion, fetish and the erotic.
boek
Keywords: Fashion